BEYOND ONE’S OWN MASTERY: ON THE NORMATIVE FUNCTION OF HATE SPEECH - Waked, Bianca M. (My University, 2018)
This thesis calls for a reconfiguration of hate speech as a primarily normative phenomenon. All hate speech strives to weaken the social-moral normative status of its targets and in doing, justifies violence against its target. In light of this normative function, the harm of hate speech is reconsidered. Against traditional defenders of hate speech regulation, I claim that individual and collective harm is a highly likely, but not a necessary consequence of hate speech, while intrinsic harm and reckless risk necessarily follow from hate speech’s normative capacity. In light of the normative origin of such harms, a societal response with normative clout is required. However, while individual responses are insufficient to block the normativity of hate speech, I suggest that the legal system is characteristically well-suited to do so.
Keywords: Hate Speech; Philosophy of Law; Normativity; Philosophy of Language